Pulmonary hypertension in patients with sarcoidosis: A single-center experience - (:unkn) unknown (AVES, 2020)
Objective: Sarcoidosis is a systemic granulomatous disease rarely complicated by pulmonary hypertension (PH). The prevalence of PH in sarcoidosis is unclear and has differences between ethnic groups. This study aimed to investigate the prevalence and predictors of PH in a Turkish cohort. Methods: The study included 55 patients with biopsy-proven sarcoidosis in a single center. All patients underwent detailed transthoracic echocardiography (TTE) to assess the probability of PH as recommended. Right heart catheterization (RHC) was performed for patients with intermediate-high risk of PH. Patients with mean pulmonary artery pressure >20 mm Hg by RHC were defined as PH. Demographic and clinical characteristics, laboratory data, spirometry, 6-min walk test, and TTE were compared between low and intermediate-high risk PH groups. Results: The probability of PH was low with 47 patients. Eight patients had intermediate-high probability of PH, and two of them refused to undergo RHC. Of six intermediate-high probability patients, three had PH, and all of them had post-precapillary PH. The prevalence of PH in sarcoidosis was 5.5% (3/55). Six-minute walk distance (6 MWD) and diastolic parameters (E/A ratio, E' wave, and left atrial volume) were significantly lower, and New York Heart association class and N-terminal probrain natriuretic peptide (NT-proBNP) level were higher in intermediate-high risk PH patients compared with low-risk PH patients. Conclusion: The frequency of PH in sarcoidosis was 5.5% in a Turkish cohort. NT-proBNP, 6 MWD, diastolic function parameters, and myocardial strain parameters can be useful predictors of PH in patients with sarcoidosis, besides known echocardiographic parameters.
Keywords: brain natriuretic peptide; sarcoidosis; 6-minute walk test; pulmonary hypertension; SPECKLE TRACKING ECHOCARDIOGRAPHY; ARTERIAL-HYPERTENSION; EUROPEAN ASSOCIATION; AMERICAN SOCIETY; RECOMMENDATIONS; GUIDELINES; OUTCOMES; UPDATE